1974
DOI: 10.1111/j.1432-1033.1974.tb03850.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Forms of Rat‐Liver Arginase. Isolation and Characterization

Abstract: Debate continues over the physical characteristics and even the existence of arginase isoenzymes. This paper gives additional support for such multiplicity and reports differences in physical characteristics among the various forms. After 2500–5000‐fold purification of rat liver arginase, three molecular forms were separated on carboxymethyl‐cellulose columns and were purified 2500–5000‐fold, 800–1000‐fold and 600–1000‐fold, respectively. The molecular forms have also been identified by chromatography in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
4
27
1
Order By: Relevance
“…The calculated K m value in both control and diabetic groups was 3.16 ± 0.18 mM, similar to the value reported (3 mM) for rat liver enzyme (Tarrab et al, 1974). Jenkinson and Grigor (1994) reported that rat liver and kidney arginases gave the K m values for the substrate, L-arginine, 14.2 and 14.4 mM, respectively.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The calculated K m value in both control and diabetic groups was 3.16 ± 0.18 mM, similar to the value reported (3 mM) for rat liver enzyme (Tarrab et al, 1974). Jenkinson and Grigor (1994) reported that rat liver and kidney arginases gave the K m values for the substrate, L-arginine, 14.2 and 14.4 mM, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…The optimum pH for the liver and kidney arginases in both control and diabetic groups is similar to that reported for other mammalian tissues (Tarrab et al, 1974;Konarska and Tomaszewski, 1975;Van Elsen and Leroy, 1975;Spector et al, 1982;Jenkinson and Grigor, 1994). However, the pH profile of arginase in kidney of diabetic rats was different from that of control rats.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Rabbit antibody raised against purified rat liver arginase was received as a gift from Dr. Raphael Palacios, Institute of Biomedical Investigation at the Autonomous University of Mexico, Mexlco City, Mexico (15). This antibody precipitated both rat and human liver arginase activity completely, the latter with lower affinity.…”
Section: Materzalsmentioning
confidence: 99%
“…Arginase from rat (Schimke, 1962;Hirsch-Kolb and Greenberg, 1968;Tarrab et al, 1974), rabbit (Vielle-Breitburd and Orth, 1972) and human (Beruter et al, 1978;Brusdeilins et al, 1985) livers has been purified and was found to consist of three identical subunits (Penninckx et al, 1974) of about 35,000 daltons. Arginase isozyme(s) that differs from the liver enzyme in catalytic, molecular and immunological properties, is present in the kidney, small intestine and lactating mammary gland (Glass and Knox, 1973;Herzfeld and Raper, 1976;Skrzypek-Osiecka et aL, 1983;Spector et al, 1983).…”
Section: Introductionmentioning
confidence: 99%